Synthesis and characterization of cassava starch nanocrystals by hydrolysis method - Md. Shahrodin, Nur Shazrynda (2014)
Cassava starch nanocrystals (CSN) has not been reported in open literature, although other starches such as rice, corn, potato and bean were widely used as the main material. Thus, the objective of this research was to investigate the possibility of synthesizing high yield of CSN at different concentrations of sulphuric acid (H2SO4). The physical, chemical and thermal properties of synthesized CSN was also investigated. Synthesized CSN was prepared by hydrolysing native cassava starch (NCS) with several concentration of H2SO4 (2.8 M, 3.0 M, 3.2 M and 3.4 M). The acid hydrolysis process took 5 days with continuous stirring speed of 300 to 400 rpm, with constant temperature of 37 °C. The hydrolysed solution of CSN underwent a centrifuging process with distilled water until it was neutralized to make sure that no acid residues remain in the CSN solution. The CSN precipitate was dried in an oven over night at 60 °C. The highest yield (1.1 %) produced was from 3.4 M CSN. Morphological test by transmission electron microscopy indicated that the samples have been destructed and degraded to be nanocrystals with a size range of 5 - 20 nm. X-ray diffraction (XRD) and 13C nuclear magnetic resonance (13C NMR) were used to indicate the type of crystallinity for both NCS and CSN. XRD illustrated that NCS was a C – type patterns, however after hydrolysed (CSN), the crystallinity changed to B – type crystalline starch. This result was also proven in 13C NMR resonance pattern. Fourier transform infrared (FTIR) spectra showed a few peaks shifted after hydrolysis, most of the changes were due to the hydrogen bonding in starch molecules which proved that there were alteration in the inter and intra-molecular hydrogen bonding of starch molecules. The thermal properties showed that glass transition temperature (Tg) was gradually increased as the concentration of the acid increased. This was due to the more energy needed to disrupt crystalline structures which were formed during synthesis process.